2014
DOI: 10.9790/0853-13189097
|View full text |Cite
|
Sign up to set email alerts
|

The Eradication of Yaws in the Sub-District of Tongkuno, District of Muna, Indonesia: Towards A Community-Based Participative Surveillance Model

Abstract: Background: -This paper describes the findings of a research on Yaws Eradication Program in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Munir et al [ 36 ] reported a survey among health workers in primary health center, elementary school teachers, and parents in Muna, Southeast Sulawesi. They were asked about yaws to measure their knowledge about sign and symptoms, causative agent, and therapy for yaws.…”
Section: Yawsmentioning
confidence: 99%
“…Munir et al [ 36 ] reported a survey among health workers in primary health center, elementary school teachers, and parents in Muna, Southeast Sulawesi. They were asked about yaws to measure their knowledge about sign and symptoms, causative agent, and therapy for yaws.…”
Section: Yawsmentioning
confidence: 99%